Edirectives : guide to European Union law on e-commerce : commentary on the directives on distance selling, electronic signatures, electronic commerce, copyright in the information society, and data protection /: guide to European Union law on e-commerce : commentary on the directives on distance selling, electronic signatures, electronic commerce, copyright in the information society, and data protection. (2002) - Unknown
No abstract available